2017
DOI: 10.1088/1674-1056/26/6/067901
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/Mo2C heterostructure directly grown by chemical vapor deposition

Abstract: Graphene-based heterostructure is one of the most attractive topics in physics and material sciences due to its intriguing properties and applications. We report the one-step fabrication of a novel graphene/Mo 2 C heterostructure by using chemical vapor deposition (CVD). The composition and structure of the heterostructure are characterized through energydispersive spectrometer, transmission electron microscope, and Raman spectrum. The growth rule analysis of the results shows the flow rate of methane is a mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…In addition to the Mo‐C peaks at 228 and 231.2 eV, the peaks at binding energies of 228.4, 232.2, 232.7, 235.5 eV are assigned to Mo +4 and Mo +6 species, which can be attributed to the surface oxidation of Mo 2 C in air 33,34 . The high resolution C 1s spectra (Figure 2B) of the sample can be well‐fitted into two peaks, indicating the formation of graphene (sp 2 hybridized C‐C at 284.3 eV) 35 along with Mo 2 C (Mo‐C at 284.2 eV), 33 in line with previous works where they demonstrated the formation of graphene along with Mo 2 C crystals at a high ratio of CH 4 to H 2 flow rate (≥1:60) 14‐16 …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In addition to the Mo‐C peaks at 228 and 231.2 eV, the peaks at binding energies of 228.4, 232.2, 232.7, 235.5 eV are assigned to Mo +4 and Mo +6 species, which can be attributed to the surface oxidation of Mo 2 C in air 33,34 . The high resolution C 1s spectra (Figure 2B) of the sample can be well‐fitted into two peaks, indicating the formation of graphene (sp 2 hybridized C‐C at 284.3 eV) 35 along with Mo 2 C (Mo‐C at 284.2 eV), 33 in line with previous works where they demonstrated the formation of graphene along with Mo 2 C crystals at a high ratio of CH 4 to H 2 flow rate (≥1:60) 14‐16 …”
Section: Resultsmentioning
confidence: 93%
“…Secondly, CH 4 flow rate is also very critical not only because it is the carbon source in Mo 2 C, but also the excess amount results in the formation of graphene, which may act as an additional diffusion barrier in the supply of Mo atoms 17 . Although various groups have mentioned simultaneous growth of graphene and Mo 2 C, there are conflicts in the positional relationship between graphene and Mo 2 C as well as their formation mechanism 14‐17,24 . For example, while Geng et al claims the evolution of graphene beneath 2D Mo 2 C, 14 with similar growth conditions, Deng et al suggests the formation of graphene on top of Mo 2 C crystals 15 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, their advanced TEM data show that the thin layers are single crystals of orthorhombic α‐Mo 2 C and that they are free of defects . Geng et al, Geng et al, and Deng et al reported similar AFM, optical microscopy, and TEM data on the structure and morphology of 2D‐α‐Mo 2 C/graphene hybrid materials …”
Section: Introductionmentioning
confidence: 88%